Misinformation and Its Effects on Individuals and Society from 2015 - 2023: A Mixed Methods Review Study - Della Giustina, Nicholas (My University, 2023)
The historical study of misinformation has been ongoing for decades and the modern era is no exception. This paper is a systematic, mixed methods review that explores the available peer-reviewed literature on misinformation that has been generated since 2015. Seven academic articles are systematically reviewed and thematically analyzed. In order to tie the effects of misinformation through the individual and to greater cultural events through motivated action, this paper will define and utilize a theoretical framework of generalized allostatic effect. This framework postulates that misinformation causes hypertension which leads to mood disorders that in turn foment into misinformed action. Misinformation distorts the perception of reality and corrupts the human practice of collective sense-making during times of crisis which subsequently delays solution-based responses. Thematic analyses were conducted to examine eight articles selected for the mixed methods review. Themes include memory distortion, continued influence effect and technological concerns. Results of this study find that misinformation is a big problem in American culture, causing stress in people which can develop into mental illness and disrupting solution-based efforts during crises. This study also found that more research is urgently needed in order to develop methods for mitigating the effects of misinformation.